MYCOLOGICAL ASSESSMENT OF INDOOR AIR QUALITY: CROSS-SECTIONAL STUDY OF SELECTED PRIVATE HOSPITALS IN DUTSE, JIGAWA STATE, NORTHWEST NIGERIA - Adeniyi Olarewaju Adeleye; Sunday Nicholas; Peter Gimba Shiaka; Mohammed Bello Yerima (Journal CleanWAS)
The purity of breathable air in an indoor environment is one of the factors that determines how healthy the inhabitants are. In order to evaluate the mycological indoor air quality of a few chosen private hospitals in Dutse metropolitan, this study was carried out. To choose the three (3) private hospitals that agreed to the study’s conduct, a purposive sampling technique was used. The settle plate method was adopted to isolate fungi in the morning, afternoon, and evening using eighty one (81) sterile sabouraud dextrose agar (SDA) plates. Following that, established microbiological techniques were used to identify the fungal isolates. The indoor environment of the private hospitals were extensively contaminated with fungal aerosols, according to the results, with mean fungal loads in the morning (4680 CFU/m3), afternoon (3566 CFU/m3), and evening (3016.33 CFU/m3). However, the mean fungal load obtained in Dr. Bashir hospital (4966 CFU/m3) was significantly (p< 0.05) different from other private hospitals while the mean fungal loads obtained across all the private hospitals were not significantly (p> 0.05)different from each other. Penicillium spp. (23.46%), Aspergillus flavus (7.41%), Mucor spp. (17.28%), Rhizopus spp. (13.58%) and Aspergillus niger (23.46%) were isolated across the private hospital indoor environment. The findings in this study indicate that fungal aerosols were able to accumulate in the examined indoor environment of the hospitals regardless of the sampling intervals, suggesting that they may have the ability to act as a reservoir of fungal infections. Therefore, it is advised that safety precautions should be taken in order to lessen fungal contamination in the hospitals’ indoor environment.